Relationship Between Nutrition Knowledge and Dietary Intake: An Assessment Among a Sample of Italian Adults - Scalvedi, Maria Luisa; Gennaro, Laura; Saba, Anna; Rossi, Laura (Frontiers in Nutrition, 2021)
Background: Assessing nutrition knowledge provides useful information especially if coupled with the self-perception of nutrition knowledge that could lead to bias and personal conviction. The objective of this study was to assess the nutrition knowledge and its relationship with eating habits in a group of adults. Methods: A cross-sectional study with the administration of self-reported questionnaires was conducted on a sample of 591 parents (43±5.82 years old) of primary school pupils recruited from the municipality of Rome (urban) and province (rural). The fieldwork was carried out in May 2017. An indicator to evaluate adherence to Italian dietary guidelines was developed. ANOVA (Welch’s ANOVA in case of unequal variances) and Chi-squared test were used fixing the significance level at 5% (p<0,05). Results: The percentage of correct answers to nutrition knowledge was 46%, with the expert recommendation section having the highest percentage (59%).The majority of the respondents (66%) were confident that they had a high level of nutrition knowledge. In 37% of the sample, nutrition knowledge and self-perception nutrition knowledge levels were found to be associated. 40% of the sample showed eating habits congruent with nutrition knowledge level. In the investigated sample, living in rural areas, being young, and having low school education level were factors associated with lower nutrition literacy or/and unhealthy eating habits. Conclusions: This study provided a demonstration that an assessment based on a multidimensional and multilevel approach is helpful to identify knowledge gaps and to profile critical segments to put in place targeted policy interventions.